Intraoperative photodynamic therapy of bladder cancer with alasens (results of multicenter trial) - E. V. Filonenko; A. D. Kaprin; B. Ya. Alekseev; O. I. Apolikhun; G. N. Vorozhzov; E. K. Slovokhodov; V. I. Ivanova-Radkevich; E. A. Machinskaya (Biomedical Photonics, 2014)
The results of multicenter prospective trial for efficacy of combined modality treatment: transurethral resection (TUR) + photodynamic therapy (PDT) with alasens for bladder cancer are represented in the article. Trials were organized by Research Institute of Organic Intermediates and Dyes and conducted according to clinical protocol approved by Ministry of Health of Russia, at the sites of leading Russian cancer clinical centers. The trial included 45 subjects with verified diagnosis of non-muscle-invasive bladder cancer. Patients underwent TUR of bladder with simultaneous PDT as anti-relapse treatment. Alasens was administered to patients as intravesicular instillation of 3% solution in volume of 50 ml with 1.5–2h exposure (prior to TUR). TUR was performed after instillation. PDT session was conducted immediately after the completion of TUR on a single occasion by means of combined local irradiation on tumor bed with diffuse irradiation on whole urinary bladder mucosa (light dose of local irradiation – 100 J/cm2, diffuse irradiation – 20 J/cm2). Good tolerance of the treatment was noticed, there were no complications. Among 45 patients included in the trial, 35 (78%) completed 12 month protocol follow-up without relapse. The recurrence of bladder tumor was registered in 10 (22%) cases 6–12 months after TUR+PDT including 3 patients with recurrence 6 months after treatment, 3–9 months and 4–12 months. These patients underwent repeated TUR, whereafter their follow-up in the settings of the clinical trial was disposed. Thus, PDT with alasens after TUR allowed to decrease the recurrence rate of non-muscle-invasive bladder cancer for 1st year after treatment to 22% versus 40–80% for TUR as monotherapy according to literature data. The obtained results were comparable by efficiency with TUR combined with methods of adjuvant treatment for bladder tumors (the recurrence rates for 1-year follow-up after TUR+chemotherapy – 36–44%, after TUR+BCG – 20–59%).